IMPROD biparametric MRI in men with a clinical suspicion of prostate cancer (IMPROD Trial): Sensitivity for prostate cancer detection in correlation with whole‐mount prostatectomy sections and implications for focal therapy. Issue 5 (22nd March 2019) - Merisaari, Harri; Jambor, Ivan; Ettala, Otto; Boström, Peter J.; Montoya Perez, Ileana; Verho, Janne; Kiviniemi, Aida; Syvänen, Kari; Kähkönen, Esa; Eklund, Lauri; Pahikkala, Tapio; Vainio, Paula; et al.
Abstract : Background: Prostate MRI is increasingly being used in men with a clinical suspicion of prostate cancer (PCa). However, development and validation of methods for focal therapy planning are still lagging. Purpose: To evaluate the diagnostic accuracy on lesion, region‐of‐interest (ROI), and voxel level of IMPROD biparametric prostate MRI (bpMRI) for PCa detection in men with a clinical suspicion of PCa who subsequently underwent radical prostatectomy. Study Type: Prospective single‐institution clinical trial (NCT01864135). Population: Sixty‐four men who underwent radical prostatectomy after IMPROD bpMRI performed in prebiopsy settings. Field Strength/Sequence: IMPROD bpMRI consisted of T2 ‐weighted imaging (T2 w) and three separate diffusion‐weighted imaging acquisitions with an average acquisition time of 15 minutes. Assessment: The diagnostic accuracy of prospectively reported manual cancer delineations and regions increased with 3D dilation were evaluated on the voxel level (volume of 1.17 mm 3, 1 mm 3, 125 mm 3 ) as well as the 36 ROI level. Only PCa lesions with a diameter ≥ 5 mm or any Gleason Grade 4 were analyzed. All data and protocols are freely available at:http://petiv.utu.fi/improd Statistical Tests: Sensitivity, specificity, accuracy. Results: In total, 99 PCa lesions were identified. Forty (40%, 40/99) had a Gleason score (GS) of >3 + 4. Twenty‐eight PCa lesions (28%, 28/99) were missed by IMPROD bpMRI, three (7.5%, 3/40) with GS >3 + 4. 3D dilation of manual cancer delineations in all directions by 10–12 mm (corresponding to the Hausdorff distance) was needed to achieve sensitivity approaching 100% on a voxel level. Data Conclusion: IMPROD bpMRI had a high sensitivity on lesion level for PCa with GS >3 + 4. Increasing 3D lesion delineations by 10–12 mm (corresponding to the Hausdorff distance) was needed to achieve high sensitivity on the voxel level. Such information may help in planning ablation therapies. Level of Evidence: 1 Technical Efficacy: Stage 2 J. Magn. Reson. Imaging 2019;50:1641–1650.